TNF Receptor 2 Makes Tumor Necrosis Factor a Friend of Tumors - Sheng, Yuqiao; Li, Feng; Qin, Zhihai (Frontiers in Immunology, 2018)
Tumor necrosis factor (TNF) is widely accepted as a tumor-suppressive cytokine via its ubiquitous receptor TNFR1. The other receptor, TNFR2, is not only expressed on some tumor cells, but on suppressive immune cells, including regulatory T cells and myeloid-derived suppressor cells. In contrast to TNFR1, TNFR2 diverts the tumor-inhibiting TNF into a tumor-advocating factor. TNFR2 directly promotes the proliferation of some kinds of tumor cells. Also activating immune-suppressive cells, it supports immune escape and tumor development. Hence, TNFR2 may represent a potential target of cancer therapy. Here, we focus on expression and role of TNFR2 in the tumor microenvironment. We summarize the recent progress in understanding how TNFR2-dependent mechanisms promote carcinogenesis and tumor growth; discuss the potential value of TNFR2 in cancer treatment.